Tungsten filament detection method

By inlaiding, polishing, scanning electron microscopy and analyzing the tungsten wire harness sample, the problem of difficulty in intuitively detecting the internal performance of the tungsten wire bus in the prior art is solved, and the accurate evaluation of the performance of the tungsten wire bus and the unqualified product is achieved. Identification reduces the line break rate and cost during production.

CN119470523AActive Publication Date: 2025-02-18CHANGSHA DIAT NEW MATERIAL SCI & TECH

Patent Information

Application Number
CN202411598673.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art is difficult to intuitively detect the shear resistance and internal defects inside the tungsten wire busbar, resulting in the missed inspection of unqualified tungsten wire busbars, affecting the continuity and cost of the diamond wire production process.

Method used

By sticking multiple tungsten wires into wire harness samples, inlaid in the mold, polishing and polishing, scanning electron microscopy and energy spectrum analysis technology are used to observe the defects and elemental composition of the cross-section of the tungsten wire, and determine their resistance to shear, splits and Resistance to fracture.

Benefits of technology

The intuitive detection of the internal performance of tungsten wire is realized, the recognition rate of unqualified tungsten wire busbars is improved, and the line break rate and cost in the production process of diamond wires is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470523A_ABST
    Figure CN119470523A_ABST
Patent Text Reader

Abstract

The invention discloses a tungsten filament detection method, which belongs to the technical field of tungsten filament detection, and comprises the following steps: adhering a plurality of tungsten filaments into a wire harness sample; embedding the wire harness sample into a mold hole of a mold, enabling the wire harness sample to be perpendicular to the surface of the mold, adding a cold embedding solution into the mold, closing the mold, and opening the mold and taking out after waiting for 1-3 hours; the wire harness sample is ground and polished, and the grinding mesh number ranges from 400 meshes to 5000 meshes; carrying out electron microscope scanning and energy spectrum analysis on the cross section of the wire harness sample, judging that the anti-shearing performance and the anti-splitting performance of the interior of the tungsten filament are good if the proportion of the tungsten filament with the split surface and the fractured tungsten filament is within 10%, and judging that the anti-cracking performance of the tungsten filament is good if the proportion of the C element and the O element is within 8%; defects of the cross section of the tungsten filament are visually observed through a scanning electron microscope, whether the cross section of the tungsten filament is broken or not is observed in a polishing mode, the anti-shearing capacity is judged, composition elements of an incoming bus are analyzed in an energy spectrum mode, and the advantages and disadvantages of the tungsten filament drawing process are judged according to the proportion of all the elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tungsten wire detection, and in particular to a tungsten wire detection method. Background Art

[0002] In the application field of diamond wire, the penetration rate of tungsten wire diamond wire has gradually increased, reaching about 30% in 2024, and the demand will maintain a high growth rate in the next two to three years. According to the release of Xiamen Tungsten's production and the applicability of tungsten wire diamond wire in N-type silicon wafers, it is expected that the penetration rate of tungsten wire will be about 50% in 2025; the market space growth rate in 2025 / 2026 will be nearly 90%; tungsten wire busbar will replace carbon steel wire busbar to become the mainstream of subsequent diamond wire.

[0003] The commonly used tungsten wire busbar inspection now mainly includes wire diameter, breaking force, ring diameter and appearance inspection, which cannot directly show the shear resistance and defects inside the tungsten wire. The missed inspection of unqualified tungsten wire busbar will cause the diamond wire production process to break, resulting in cost loss. Therefore, strengthening the inspection of tungsten wire busbar during the inspection process can effectively reduce costs and resource waste.

[0004] In view of this, it is necessary to propose a new technical solution to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a tungsten wire detection method to solve the problem that the internal performance of the tungsten wire cannot be directly detected in the prior art.

[0006] To achieve the above purpose, the present invention adopts the following technical means:

[0007] A tungsten wire detection method comprises the following steps:

[0008] Step 1, bonding a plurality of tungsten wires into a wire harness sample;

[0009] Step 2, embedding the wire harness sample in step 1 into the mold hole of the mold, with the wire harness sample perpendicular to the mold surface, adding a cold embedding solution into the mold and closing the mold, waiting for 1-3 hours, then opening the mold and taking out the wire harness sample;

[0010] Step 3, grinding and polishing the wire harness sample, with the grinding mesh ranging from 400 to 5000 mesh;

[0011] Step 4, performing electron microscope scanning and energy spectrum analysis on the cross section of the wire harness sample polished in step 3. If the proportion of surface split and broken tungsten wires in the wire harness sample is within 10%, it is judged that the shear resistance and splitting resistance of the tungsten wire are good. If the proportion of C element and O element is within 8%, it is judged that the tungsten wire has good anti-fracture performance.

[0012] The metallographic detection method of the present invention visually observes the defects of the cross section of the tungsten wire through a scanning electron microscope, observes whether the cross section of the tungsten wire is broken by grinding to determine the shear resistance, analyzes the component elements of the incoming busbar by an energy spectrum, and determines the quality of the tungsten wire drawing process by the proportion of each element.

[0013] As a further improvement, in step 1, the tungsten wire is cut into segments, each segment of the tungsten wire is of equal length, and each segment of the tungsten wire is glued together into a bundle with glue.

[0014] As a further improvement, the number of tungsten wires in the wire harness sample is not less than 8.

[0015] As a further improvement, the diameter of the mold hole is slightly larger than the diameter of the wire harness sample.

[0016] As a further improvement, the cold mounting solution is composed of acrylic powder and metallographic glue, and the volume ratio of the resin powder to the metallographic glue is 1:1 to 5:1.

[0017] As a further improvement, the volume ratio of the resin powder to the metallographic glue is 2:3.

[0018] As a further improvement, the preparation of the cold mounting solution comprises the following steps:

[0019] First add 20ml acrylic powder into a 50ml beaker;

[0020] Then add 20ml of metallographic glue and stir evenly;

[0021] Add 10 ml of metallographic glue and stir until the solution becomes a colloidal liquid.

[0022] As a further improvement, in step 3, the grinding time of sandpapers of different mesh sizes is not less than 5 minutes, and the grinding direction should be changed after the sandpaper is changed, so that the wear marks on the surface of the wire harness sample are shallower.

[0023] As a further improvement, in step 3, 1.5 um diamond polishing paste is used during the polishing process, and the polishing time is not less than 30 minutes.

[0024] As a further improvement, step 5 is also included: distinguishing the tungsten wire busbar and the coating by scanning with an electron microscope, drawing perpendicular midlines on any two straight lines of the busbar arc to determine the center of the busbar, marking the busbar radius and the finished wire radius through the center of the circle, and subtracting them to obtain the coating thickness.

[0025] Compared with the prior art, the present invention brings the following technical effects: the metallographic detection method of the present invention visually observes the defects of the cross section of the tungsten wire through a scanning electron microscope, observes whether the cross section of the tungsten wire is broken by grinding to determine the shear resistance, analyzes the constituent elements of the incoming busbar by an energy spectrum, and determines the quality of the tungsten wire drawing process by the proportion of each element; and this method is also suitable for the detection of the coating thickness of the finished electroplated diamond wire. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 A schematic flow chart of a tungsten wire detection method is shown;

[0028] Figure 2 A schematic diagram of the application process of the tungsten wire detection method is shown;

[0029] Figure 3 The conductive glue image before electron microscope treatment for tungsten wire detection method is shown;

[0030] Figure 4 A schematic diagram showing the electron microscopy results of different samples using the tungsten wire detection method is shown;

[0031] Figure 5 A schematic diagram of metallographic thickness measurement of tungsten wire is shown in the tungsten wire detection method.

[0032] Description of main component symbols:

[0033] 1-Wire harness sample; 2-Conductive adhesive. DETAILED DESCRIPTION

[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0035] A tungsten wire detection method comprises the following steps:

[0036] Step 1, bonding a plurality of tungsten wires into a wire harness sample;

[0037] Step 2, embedding the wire harness sample in step 1 into the mold hole of the mold, with the wire harness sample perpendicular to the mold surface, adding a cold embedding solution into the mold and closing the mold, waiting for 1-3 hours, then opening the mold and taking out the wire harness sample;

[0038] Step 3, grinding and polishing the wire harness sample, with the grinding mesh ranging from 400 to 5000 mesh;

[0039] Step 4, performing electron microscope scanning and energy spectrum analysis on the cross section of the wire harness sample polished in step 3. If the proportion of surface split and broken tungsten wires in the wire harness sample is within 10%, it is judged that the shear resistance and splitting resistance of the tungsten wire are good. If the proportion of C element and O element is within 8%, it is judged that the tungsten wire has good anti-fracture performance.

[0040] The metallographic detection method of the present invention visually observes the defects of the cross section of the tungsten wire through a scanning electron microscope, observes whether the cross section of the tungsten wire is broken by grinding to determine the shear resistance, analyzes the component elements of the incoming busbar by an energy spectrum, and determines the quality of the tungsten wire drawing process by the proportion of each element.

[0041] Example

[0042] The present invention provides a tungsten wire detection method for detecting the performance of tungsten wire and detecting the element composition of tungsten wire. The process flow of the tungsten wire detection method is mainly divided into the following steps: segmenting the tungsten wire busbar, bonding into bundles, metallographic cold mounting, sample grinding and polishing, scanning electron microscope scanning and energy spectrum analysis.

[0043] More specifically, see Figure 1 , the tungsten wire detection method includes the following steps:

[0044] Step S101, bonding a plurality of tungsten wires into a wire harness sample;

[0045] Step S102, embedding the wire harness sample in step 1 into the mold hole of the mold, with the wire harness sample perpendicular to the mold surface, adding a cold embedding solution into the mold and closing the mold, waiting for 1-3 hours, then opening the mold to take out the wire harness sample;

[0046] Step S103, grinding and polishing the wire harness sample, with the grinding mesh number ranging from 400 mesh to 5000 mesh;

[0047] Step S104, performing electron microscope scanning and energy spectrum analysis on the cross section of the wire harness sample polished in step 3. If the proportion of surface split and broken tungsten wires in the wire harness sample is within 10%, it is determined that the shear resistance and splitting resistance of the tungsten wire are good. If the proportion of C element and O element is within 8%, it is determined that the tungsten wire has good anti-fracture performance.

[0048] More specifically, see Figure 2In step 1, the tungsten wire segmentation is to cut the incoming tungsten wire into segments of the same length, and it is necessary to ensure that the length of each segmented tungsten wire is consistent and presents a straight line; preferably, the number of segments is preferably 8 to 40 to meet the conductivity requirements, and more preferably, the number of segments is preferably 10 to 20, and this embodiment is illustrated with 10 segments.

[0049] More specifically, see Figure 2 In step 1, multiple segmented tungsten wires are bonded into a bundle, the purpose of which is to bond the fine segmented tungsten wires into a bundle through glue, which is conducive to later scanning electron microscope observation and improving conductivity. The glue can be 502 glue or other glue, preferably 502 glue. Preferably, during the bonding process, it is necessary to ensure that each tungsten wire is only bonded, and the gaps between the wires are minimized as much as possible, and the bonded tungsten wire bundle sample presents a straight line shape.

[0050] More specifically, see Figure 2 , the metallographic cold mounting in step 2 mainly uses a mounting machine to mount the bundled tungsten wire harness sample in the resin. Among them, the cold mounting process mainly requires the use of a mounting machine, a mounting mold, resin powder and metallographic glue, and the volume ratio of resin powder to metallographic glue is 1:2 to 5:1. The resin powder is preferably acrylic powder, and the volume ratio of acrylic powder to metallographic glue is 2:3. If the solidification speed needs to be accelerated, the volume ratio of acrylic powder to metallographic glue needs to be increased. However, a too high volume ratio of acrylic powder to metallographic glue will have an adverse effect on subsequent electron microscope scanning. After countless repeated experiments, the optimal volume ratio of acrylic powder to metallographic glue is 2:3, which can solidify within an appropriate time without adversely affecting the test results.

[0051] The inlay process mainly includes mold fixing, wire harness sample fixing, inlay solution preparation, inlay machine mold closing and mold opening and removal.

[0052] First, fix the inlay mold on the inlay machine, drill a small hole in the center of the inlay mold, and the hole diameter is slightly larger than the diameter of the tungsten wire harness sample; then pass the tungsten wire harness sample through the inlay mold, the tungsten wire of the harness sample is perpendicular to the surface of the inlay mold, and ensure that the harness sample is inlaid in the middle of the inlay mold; fill the gap at the bottom of the inlay mold with 502 glue to avoid leakage when closing the mold; first add 20ml of acrylic powder to a 50ml beaker, then add 20ml of metallographic glue, stir evenly and then add 10ml of metallographic glue, the stirred solution will present a colloidal liquid metallographic solution; pour the prepared metallographic solution into the inlay mold, and take it out after the inlay machine closes the mold for 1 hour. Among them, the waiting time for mold opening is inversely proportional to the volume ratio of high acrylic powder and metallographic glue, that is, the larger the volume ratio of high acrylic powder and metallographic glue, the shorter the waiting time for mold opening. The specifications of the inlay mold are designed according to the size of the scanning electron microscope, and the radius and height can be freely selected. Among them, the inlay mold is preferably a cylindrical mold with a radius of 30 mm and a height of 30 mm.

[0053] At present, metallographic glue uses epoxy glue, and the curing time of epoxy glue is still relatively long. In order to improve the time efficiency of detection, preferably, the metallographic glue uses a high-efficiency metallographic inlay solidifying glue, which is composed of the following components: 30 parts of bisphenol A epoxy resin, 60 parts of ethyl acetate, 0.2 parts of inhibitor, and 9.8 parts of monofunctional-multifunctional active diluent. The production step is to mix the above-mentioned 30 parts of bisphenol A epoxy resin, 60 parts of ethyl acetate, 0.2 parts of inhibitor and 9.8 parts of monofunctional-multifunctional active diluent, and shake and mix evenly at room temperature after sealing. The solidification time of the metallographic inlay solidifying glue will be shortened to less than 40 minutes, and the transmittance after curing can be as high as 99% or more.

[0054] More specifically, the grinding and polishing of the wire harness specimens is based on materials science metallographic grinding, with the grinding mesh ranging from 400 to 5000. It is mainly performed on a grinder. Each type of sandpaper requires at least 5 minutes of grinding, and the grinding direction needs to be changed after changing the sandpaper to make the wear marks on the surface of the metallographic sample shallower.

[0055] First, grind with 400 grit for 10 minutes to make the surface of the wire harness sample smooth without any pits or protrusions; secondly, grind with 800 grit sandpaper for 5 minutes. During the grinding process, ensure that the grinding surface of the wire harness sample is flat and smooth; then grind with 1500 grit sandpaper for 5 minutes to improve the grinding accuracy; continue to grind with 3000 grit sandpaper for 5 minutes to further improve the surface smoothness of the wire harness sample; finally, grind with 5000 grit sandpaper for 5 minutes to complete the grinding process.

[0056] After grinding, polish with 1.5um polishing paste on the polishing cloth for 30 minutes; the surface of the wire harness sample after grinding and polishing is flat and extremely smooth; after grinding, observe the wear marks on the surface of the tungsten wire in the metallographic wire harness sample through an optical microscope. If the wear marks are too deep, re-grinding and polishing are required.

[0057] More specifically, see Figure 3 , the scanning electron microscope scanning and energy spectrum analysis in step 4 mainly include electron microscope sample preparation, electron microscope observation and result review; the process of electron microscope sample preparation mainly involves sticking conductive glue 2 on the wire harness sample 1 after grinding and polishing, and the conductive glue 2 is attached to the measuring surface of the wire harness sample 1, specifically distributed around the cross section of the tungsten wire of the wire harness sample 1, and cannot block the cross section of the tungsten wire of the wire harness sample 1, wherein the conductive glue 2 is attached around the tungsten wire of the wire harness sample 1, the purpose is to increase the conductivity of the wire harness sample 1, and accurately locate the position of the tungsten wire. During the electron microscope observation process, the brightness and contrast of the electron microscope parameters need to be adjusted to ensure that the cross section of the tungsten wire can be clearly observed, and the cross section of the tungsten wire is intercepted and the energy spectrum is taken; during the result review process, the internal shear resistance and splitting resistance of the tungsten wire are mainly judged by observing the proportion of surface split and broken tungsten wires in the tungsten wire. If the proportion reaches 10%, it is considered that the shear resistance and splitting resistance of the tungsten wire are unqualified, and the batch of tungsten wires are judged to be unqualified. Among them, during the scanning electron microscope measurement process, the energy spectrum analysis adopts the surface scanning method, and the electron microscope mode adopts the backscattering mode.

[0058] In the energy spectrum analysis, the proportion of W, C, and O elements is mainly analyzed to judge the performance of tungsten wire. Among them, the presence of C and O impurities greatly increases the concentration of vacancy defects in W. The oxides, tungsten carbides, and nitrides in the tungsten wire are precipitated at the grain boundaries, weakening the grain boundary effect, causing various obstacles to dislocation movement, and promoting crack formation; C and O elements are enriched at the fracture of tungsten wire, which are the main grain boundary impurities of tungsten and the basic cause of tungsten embrittlement.

[0059] Therefore, the fracture resistance is mainly reflected in the element proportion of C element and O element in the energy spectrum range. Taking the C element content and O element content of Xiamen tungsten as the standard, the total content proportion of C element and O element is less than or equal to 5%, which is considered excellent; 5%-8%, which is considered good; and above 8% is considered unqualified.

[0060] See also Figure 4 , the following two examples are used for comparison and explanation:

[0061] In Example 1, tungsten busbars from two different manufacturers were analyzed respectively. The results showed that sample 1 had 5 torn tungsten wires and a total of 15 embedded wires, accounting for 33.3% of the torn wires, and was considered an unqualified product; sample 2 had 0 torn tungsten wires, and was considered excellent; the energy spectrum results of the samples before and after are shown in the table. Sample 1 had a carbon and oxygen element ratio of 5.04%, which was judged to be good; sample 2 had a carbon and oxygen element ratio of 4.27%, which was judged to be excellent.

[0062] sample Oxygen content Carbon content Sample 1 2.61% 2.43% Sample 2 2.51% 1.76%

[0063] Based on Example 1, the incoming tungsten wires were screened. As shown in the following table, batch 1 was not subjected to the quality inspection method of the present invention, and the wire breakage rate was 10.3%; batch 2 was subjected to the quality inspection method of the present invention, and the wire breakage rate was 3.1%. After the quality inspection method of the present invention was applied, the wire breakage rate of the electroplated diamond wire was significantly reduced.

[0064] Sample batch Incoming quantity / roll Screening quantity / roll Number of rolls / roll Number of broken wires / roll Batch 1 350 0 350 36 Batch 2 350 32 318 10

[0065] More specifically, the detection method of the present invention can be applied to the coating detection of finished electroplated diamond wires, such as Figure 5 As shown in the figure, under the condition of scanning electron microscope, the tungsten wire busbar and the coating can be clearly distinguished. The center of the busbar can be determined by making perpendicular lines on any two straight lines of the busbar arc. The radius of the busbar and the radius of the finished wire can be marked through the center of the circle. The thickness of the coating can be obtained by subtracting them.

[0066] Compared with the traditional method of measuring breaking force and torque, the detection method of the present invention is more accurate. It can not only evaluate the shear resistance of the tungsten wire based on the tearing, but also evaluate its fracture resistance based on the content of C and O elements in the tungsten wire, and can also detect the thickness of the finished diamond wire coating.

[0067] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0068] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A tungsten wire detection method, characterized in that: The following steps are involved: Step 1, bonding a plurality of tungsten wires into a wire harness sample; Step 2, embedding the wire harness sample in step 1 into the mold hole of the mold, with the wire harness sample perpendicular to the mold surface, adding a cold embedding solution into the mold and closing the mold, waiting for 1-3 hours, then opening the mold and taking out the wire harness sample; Step 3, grinding and polishing the wire harness sample, with the grinding mesh ranging from 400 to 5000 mesh; Step 4, performing electron microscope scanning and energy spectrum analysis on the cross section of the wire harness sample polished in step 3. If the proportion of surface split and broken tungsten wires in the wire harness sample is within 10%, it is judged that the shear resistance and splitting resistance of the tungsten wire are good. If the proportion of C element and O element is within 8%, it is judged that the tungsten wire has good anti-fracture performance.

2. The tungsten wire detection method according to claim 1, characterized in that: In the step 1, the tungsten wire is cut into segments, each segment of the tungsten wire is equal in length, and each segment of the tungsten wire is glued together into a bundle with glue.

3. The tungsten wire detection method according to claim 1, characterized in that: The number of tungsten wires in the wire harness sample shall not be less than 8.

4. The tungsten wire detection method according to claim 1, characterized in that: The aperture of the mold hole is slightly larger than the diameter of the wire harness sample.

5. The tungsten wire detection method according to claim 1, characterized in that: The cold mounting solution consists of acrylic powder and metallographic glue, and the volume ratio of the resin powder to the metallographic glue is 1:1 to 5:

1.

6. The tungsten wire detection method according to claim 1, characterized in that: The volume ratio of the resin powder to the metallographic glue is 2:

3.

7. The tungsten wire detection method according to claim 6, characterized in that: The preparation of the cold mounting solution comprises the following steps: First add 20ml acrylic powder into a 50ml beaker; Then add 20ml of metallographic glue and stir evenly; Add 10 ml of metallographic glue and stir until the solution becomes a colloidal liquid.

8. The tungsten wire detection method according to claim 1, characterized in that: In the step 3, the grinding time of sandpapers with different mesh sizes is not less than 5 minutes, and the grinding direction should be changed after the sandpaper is changed, so that the wear marks on the surface of the wire harness sample are shallow.

9. The tungsten wire detection method according to claim 1, characterized in that: In step 3, 1.5 um diamond polishing paste is used for polishing during the polishing process, and the polishing time is not less than 30 minutes.

10. The tungsten wire detection method according to claim 1, characterized in that: It also includes step 5: distinguish the tungsten wire busbar and the coating by scanning with an electron microscope, draw perpendicular midlines on any two straight lines of the busbar arc to determine the center of the busbar, mark the busbar radius and the finished wire radius through the center, and subtract them to get the coating thickness.

Citation Information

Patent Citations

  • Gold phase sample fabrication device and method of diamond wire

    CN109283027A

  • Method for preventing appearance of diamond wire from generating yellow spot defects in production process

    CN111270279A

  • Method for detecting microstructure and phase structure of tungsten and molybdenum wire

    CN117191846A

  • Continuous glass fiber monofilament diameter testing method

    CN118500273A

  • TEM / SEM sample preparation

    US6734427B1

Cited By

  • Tungsten alloy wire cold inlaying mold and device and section sample preparation method

    CN121113642A